Produktivitas Tanaman Palmarosa (Cymbopogon martinii) pada Tanah Ultisol dengan Pemberian Beberapa Pupuk Organik - Erma Suryani; Herwita Idris (JURNAL GALUNG TROPIKA, 2021)
Palmarosa plant (Cymbopogon martini: Poaceae) comes from East India and Turkey, and in Indonesia, it is known as Palmarosa grass. This plant is an essential plant with the name Palmarosa Oil. Besides being useful as a cosmetic ingredient, it can also be an active ingredient in vegetable pesticides. This study aimed to see the effect of applying organic fertilizer to Ultisol soil planting media on the production and quality of Palmarosa plants. The study was conducted at the Laing Experimental Garden, Solok Agricultural Plant Assessment and Research Installation, West Sumatra. Palmarosa plants used were 1 month old in the nursery and transferred to plastic bags measuring 30 x 40 cm. The study was arranged using a Randomized Block Design (RBD) with the following treatments Ultisol soil + Seraiwangi ash (TA), Ultisol soil + manure (TP), Ultisol soil + manure + compost (TK), and positive control andosol soil (K). Comparison of ultisol soil with organic fertilizer 1:1. Each treatment was repeated 8 times, and each replication consisted of 10 sample plants. Observations were made every 15 days after the plants were 15 days after planting. The results showed that the application of organic fertilizer on Ultisol soil + manure + compost showed the best vegetative growth in plant height growth, the number of tillers, leaf length, leaf width, and crown width. While the geraniol content is 81.04% and the oil yield is 0.31%.